On the Referential Function of Intuition - Hemmo Laiho (Brasilian Kant Society * Campinas Section, 2022)
In contemporary terms, this short paper is about perceptual reference. In Kant's terms, the topic is intuition. The main explanandum is that intuition can indeed be understood in terms of perceptual reference. More specifically, I examine two issues with two intermingled questions: How, on the one hand, should intuition be understood when it comes to perceptually referring to locally present macroscopic objects, such as chairs and tables? How, on the other hand, should intuition be understood when it comes to perceptually referring to huge objects that cannot be perceptually present to us in their entirety, such as oceans, galaxies, and ultimately the world itself?